The Relationship between Quality of Work Life and Demographic - Rao , Kaur; Arora, R.S.; Vashisht, A K (Gyan Management Journal, 2013)
Quality of work life (QWL) is a muWfaceted concept implying concern for members of an organization.·-:·: